2017
DOI: 10.1158/1078-0432.ccr-16-0564
|View full text |Cite|
|
Sign up to set email alerts
|

Ovarian Cancers Harbor Defects in Nonhomologous End Joining Resulting in Resistance to Rucaparib

Abstract: DNA damage defects are common in ovarian cancer and can be used to stratify treatment. Although most work has focused on homologous recombination (HR), DNA double-strand breaks are repaired primarily by nonhomologous end joining (NHEJ). Defects in NHEJ have been shown to contribute to genomic instability and have been associated with the development of chemoresistance. NHEJ was assessed in a panel of ovarian cancer cell lines and 47 primary ascetic-derived ovarian cancer cultures, by measuring the ability of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…In contrast, some drugs in our test such as cisplatin have been reported to be cross‐resistant to PARPi in both clinical and preclinical studies . However, cisplatin was shown not to be cross‐resistant to rucaparib in ovarian cancers defective for nonhomologous end joining . All our PARPi‐resistant PTEN‐deficient variants are not resistant to cisplatin (resistance factor: 0.62‐0.76) either.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, some drugs in our test such as cisplatin have been reported to be cross‐resistant to PARPi in both clinical and preclinical studies . However, cisplatin was shown not to be cross‐resistant to rucaparib in ovarian cancers defective for nonhomologous end joining . All our PARPi‐resistant PTEN‐deficient variants are not resistant to cisplatin (resistance factor: 0.62‐0.76) either.…”
Section: Discussionmentioning
confidence: 71%
“…[31][32][33][34] However, cisplatin was shown not to be cross-resistant to rucaparib in ovarian cancers defective for nonhomologous end joining. 35 [37][38][39][40] or ATM 41 -deficient breast [37][38][39]41 or ovarian cancer cells. 40 For the first time, our results reveal that loss of 53BP1 also dominantly mediates the resistance of PTEN-deficient glioblastoma cells to different PARPi, strongly suggesting that loss of 53BP1 is a relatively universal mechanism responsible for PARPi resistance at different conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that cells depleted of DNA-PKcs or treated with DNA-PK inhibitor induced IR-induced RAD51 foci formation [37]. We found that the effects of a DNA-PK inhibitor on RAD51 nucleofilament formation and HR function mainly occurred in G1-phase cells, while no obvious changes occurred in G2 cells.…”
Section: Discussionmentioning
confidence: 45%
“…Resistance to rucaparib has also been demonstrated in ovarian cancer tumor cells possessing NHEJ defects. NHEJ plays a significant role in the repair of double-strand DNA breaks, is independent of HR function, and is associated with resistance to rucaparib in ex vivo primary cultures 46. Other mechanisms of resistance such as hypomorphic activity of mutant BRCA1 alleles, upregulation of drug efflux pumps, and reconfiguration of the cellular DNA damage response are still under study 44…”
Section: Resultsmentioning
confidence: 99%